Comparative proteomic profiling of human dental pulp stem cells and periodontal ligament stem cells under in vitro osteogenic induction. (May 2018) - Wang, He; Ma, Dandan; Zhang, Xiaoyi; Xu, Shuaimei; Ning, Tingting; Wu, Buling
Highlights: Osteoinduced DPSCs and PDLSCs share a wide range of expressed proteins. Differentially expressed proteins distinguish osteoinduced DPSCs and PDLSCs. HSPB1 may contribute to the higher mineralization capacity of PDLSCs than DPSCs. Higher S100A10 and S100A11 may contribute to higher migration capacity of PDLSCs. Osteoinduced PDLSCs undergoes a more active cytoskeleton transformation than DPSCs. Abstract: Objective: This study aimed to compare the proteomic profiling of human dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PDLSCs) under in vitro osteogenic induction, which imitates the microenvironment during osteo-/odontogenesis of DPSCs and PDLSCs. Design: The proteomic profiles of osteoinduced DPSCs and PDLSCs from a single donor were compared using the isobaric tag for relative and absolute quantitation (iTRAQ) technique and subsequent bioinformatics analysis. Results: A total of 159 differentially expressed proteins in PDLSCs and DPSCs were identified, 82 of which had a higher expression level in PDLSCs, while 77 were more highly expressed in DPSCs. Among these enriched proteins, certain members from the collagen, heat shock protein and protein S100 families may distinguish osteoinduced PDLSCs and DPSCs. Gene ontology (GO) classification revealed that a large number of the enriched terms distinguishing PDLSCs and DPSCs are involved in catalytic activity, protein binding, regulation of protein metabolic processes and response to stimulus. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated several involved pathways, including the fatty acid biosynthesis pathway, pantothenate and CoA biosynthesis pathway, arachidonic acid metabolism pathway and PPAR signaling pathway. Further verification showed that the mineralization and migration capacities of PDLSCs were greater than those of DPSCs, in which heat shock protein beta-1, Protein S100-A10 and S100-A11 may play a part. Conclusions: Less than 5% of the differentially expressed proteins make up the comparative proteomic profile between osteoinduced PDLSCs and DPSCs. This study helps to characterize the differences between osteoinduced PDLSCs and DPSCs in vitro.